Pedestrian bridge over the Carpinteira Valley, Covilhã (2003–2009) - Sequeira, M. (Flashback: Carrilho da Graça, 2022)
The Pedestrian Bridge over the Carpinteira Valley was designed as part of a plan defined for the city of Covilhã by Nuno Teotónio Pereira in the context of the Polis Programme, which aimed to iron out the diference in height of the hilly city whose urbanisation had long since expanded beyond the valleys. Nestled at the foot of the southern end of the Serra da Estrela mountains, this bridge establishes a connection between the city centre and the peripheral district of Penedos Altos, located on the opposing slope. Perpendicular to the water line and on the abrupt granite slopes of the stream, in the form of the Greek letter ?, the new bridge crosses the valley and celebrates the relationship between the Serra da Estrela mountains and the vast and fertile landscape of Cova da Beira. The connections to the mooring points are established from this straight arch in accordance with the most favourable geometry, giving rise to a sinuous design. This project highlights Carrilho da Graça’s intention to extend architecture’s field of action to programmes not traditionally assigned to the discipline.